Flow, packing and compaction properties of novel coprocessed multifunctional directly compressible excipients prepared from tapioca starch and mannitol. (3rd October 2013) - Adeoye, Oluwatomide; Alebiowu, Gbenga
Abstract: Novel multifunctional excipients were prepared by coprocessing tapioca starch with mannitol using two methods viz; co-grinding and co-fusion. The flow, packing and compaction properties of the native and novel excipients were evaluated by using density, Hausner's ratio, angle of repose, the maximum volume reduction, consolidation index, the rate of consolidation, angle of internal friction, morphological properties, Heckel analysis, tensile strength and dilution potential as evaluation parameters. The study revealed that the method of coprocessing, particle size and particle shape influenced the properties of the resulting novel excipients. Co-grinding was less effective than co-fusion in the preparation of excipients with enhanced properties. The study concluded that coprocessing tapioca starch and mannitol will enhance the flow, packing and compaction properties of the novel excipient and that the co-fusion method of coprocessing would produce novel excipients with enhanced direct compression potential compared to the co-grinding method.